Contribution to the taxonomy and distribution of Aciculidae (Mollusca: Gastropoda: Caenogastropoda) in Albania and the surroundings - Lika, Romilda; Deli, Tamás; Paparisto, Anila; Erőss, Zoltán P.; Fehér, Zoltán (Zootaxa, 2021)
Reviewing historical and recently collected material of family Aciculidae from Albania and the neighbouring region, we synonymized two species and one subspecies, namely Platyla corpulenta Subai, 2009 under Platyla procax Boeters, E. Gittenberger & Subai, 1989; Platyla ceraunorum A. Reischütz, N. Steiner-Reischütz & P. L. Reischütz, 2016 under Platyla similis (Reinhardt, 1880) and Renea kobelti albanica Boeters, E. Gittenberger & Subai, 1989 under Renea kobelti (A. J. Wagner,1910). Four aciculid species are first mentioned for Albania: Platyla similis and Platyla procax that replace their junior synonyms; and Platyla feheri Subai, 2009 and Platyla gracilis (Clessin, 1877) that are new to the country. Furthermore, new distribution data are provided for Platyla albanica Subai, 2012, Platyla banatica (Rossmässler, 1842), Platyla wilhelmi (A. J. Wagner, 1910) and Renea kobelti (A. J. Wagner, 1910).In the light of new distribution data, their conservation statuses according to IUCN criteria are assessed at the national level and, when necessary, are re-assessed at global level.